SERVICE LEARNING CHRONICLES: A DEEP DIVE INTO THE IMPACT OF VOLUNTEERISM ON SHENZHEN UNIVERSITY’S EDUCATIONAL LANDSCAPE - Minghui , Li; Wu, Xiaoyan (Top Educational Review Journal (TERJ), 2024)
Volunteering in higher education institutions plays a pivotal role in fostering students’ values, character development, and active engagement in societal progress. Shenzhen, as the pioneer city in China to establish a "City of Volunteers" in 2011, initiated the concept of "Volunteer Campuses" within local institutions. Through effective institutional oversight, brand development, and infrastructure enhancement, universities have integrated volunteer service into their campus culture, profoundly impacting young minds and contributing to the cultivation of a culture of volunteerism and character development. Engaging in volunteer activities within higher education institutions has a profound impact on students’ principles and worldviews. Firstly, it instills a sense of social responsibility and dedication in students, as they directly witness society’s challenges and difficulties. This firsthand experience fosters empathy and compassion towards marginalized communities, motivating students to reflect on issues of social justice and equity, thereby nurturing their willingness to actively assume societal responsibilities. Secondly, volunteer service provides students with a practical platform to translate their principles and beliefs into tangible actions. Theoretical knowledge acquired in the classroom gains real-world application through experiential learning. By actively participating in volunteer service initiatives, students have the opportunity to implement their principles and convictions in concrete ways, fostering a deepened sense of commitment and accomplishment derived from serving others